Cattleya forbesii x Cattleya bowringiana: a new hybrid of Cattleya orchid - Colombo,Ronan Carlos (2017)
Abstract The hybrid between Cattleya forbesii x Cattleya bowringiana shows flowers of lilac coloration, labellum with a light yellow center and striated with purple stripes of the same tone of other floral whorls. The plant flourished four years after seeding and produced, on average, six flowers.